PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA DALAM MENAMPUNG DAN MENYALURKAN ASPIRASI MASYARAKAT DESA DI DESA KOTO TUO KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI TAHUN 2015 - Dahaban Daus; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine the implementation of the function of Village Consultative Agency in accommodating and channeling the aspirations of village communities in the Village Koto Tuo Kuantan Tengah District Kuantan Singingi Year 2015. This study uses qualitative research methods with descriptive research type, which can be interpreted as a process of solving problems investigated by describing the state of research subjects based on the facts found.This research found that the function of BPD in accommodating the aspirations of the community has not been implemented maximally because it has never conducted an activity that is accommodating the aspirations of the community. In channeling the aspirations of the community to the village head is still poorly implemented. Because all the aspirations that come from the community there is no follow-up. In addressing the aspirations of the community also has not been able to address the aspirations of the community because it rarely holds meetings with in terms of discussing the problems in the village. In determining the rules and programs of village development in accordance with the aspirated or desired by the community also looks less running properly this is due to lack of understanding with the main task and function.The conclusion is that the function of BPD in accommodating and channeling people's aspirations has not been done well. As for the causes or constraints faced by BPD in accommodating, and channeling the aspirations of the community is the absence of BPD go down directly to the community causing the difficulty implemented to accommodate and channel the aspirations of the community and the lack of attention from the members of BPD to the problems of society.Keywords: BPD Function, Accommodate and Distribute People's Aspirations